Proyecto de producción de serie dramática: “Reyes”. Una propuesta de serie web para la plataforma YouTube. - Cortez Erazo, Melannie Estefania (2023)
The project carried out is a proposal for the production of the dramatic series "Reyes" oriented to the YouTube web platform. The project consists of a fiction series, in the drama genre with touches of suspense, in a total of eight episodes per season. This series tells the story of the Montero family, who after the death of one of its members, Nicole, the older sister, returns from New York. During her stay, the Peruvian state declares a quarantine due to the spread of COVID-19. It is there that Nicole will discover clues that will lead her to reveal the dark secret behind her brother's accident. The main concepts of the project are betrayal, infidelity, justice, anxiety, stress and hypocrisy. We decided to place it in the year 2020, given that we have the state of health emergency as an opportunity, in which we take advantage of the mandatory confinement as a tool to develop the conflicts of the characters. Our objective is to develop the pilot of the proposed series, in which we will develop an attractive narrative from a pessimistic point of view.